VARIABEL-VARIABEL YANG MEMPENGARUHI KEBIJAKAN HUTANG PADA PERUSAHAAN NON KEUANGAN YANG PUBLIK - APIT SUSANTI (Jurnal Bisnis dan Akuntansi, 2014)
The purpose of this research is to examine the effect of insider ownership, institutional ownership, dividend policy, asset structure, profitability, firm growth and business risk to debt policy. Data were taken from non-financial companies are listed at Indonesia Stock Exchange for three years (2009-2011). Only 45 companies meet the criteria and taken as sample. The statistical used in this research was multiple regression. The research showed that institutional ownership, asset structure, profitability and firm growth had effect to debt policy. While, insider ownership, dividend policy, and business risk had no effect to debt policy.